2017
DOI: 10.1137/15m1025384
|View full text |Cite
|
Sign up to set email alerts
|

Data Assimilation in Reduced Modeling

Abstract: This paper considers the problem of optimal recovery of an element u of a Hilbert space H from measurements of the form ℓ j (u), j = 1, . . . , m, where the ℓ j are known linear functionals on H. Problems of this type are well studied [18] and usually are carried out under an assumption that u belongs to a prescribed model class, typically a known compact subset of H. Motivated by reduced modeling for solving parametric partial differential equations, this paper considers another setting where the additional i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
155
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 115 publications
(157 citation statements)
references
References 16 publications
2
155
0
Order By: Relevance
“…Since M ⊆ M relax , one can thus construct a prior of the form (15) satisfying (2), from any combination of the subspaces (17) and scalars (18). We note that this procedure applies even if M relax is not defined via a relaxed set of parameters Θ relax as in (16).…”
Section: Some Specific Choices For M Priormentioning
confidence: 99%
See 4 more Smart Citations
“…Since M ⊆ M relax , one can thus construct a prior of the form (15) satisfying (2), from any combination of the subspaces (17) and scalars (18). We note that this procedure applies even if M relax is not defined via a relaxed set of parameters Θ relax as in (16).…”
Section: Some Specific Choices For M Priormentioning
confidence: 99%
“…choices of M prior [18]. When M prior is defined as the intersection of degenerate ellipsoids as in (15), the authors of [18] showed thatĥ corresponds to some specific point of M prior ∩ H h (namely the center of the Chebyshev ball of M prior ∩ H h ).…”
Section: Reduction Based On Point Estimatesmentioning
confidence: 99%
See 3 more Smart Citations